Improving Self Empowerment And Quality Of Life Of Patients With Type 2 Diabetes Mellitus With DEE Based On Health Promotion Model - Nian Afrian Nuari; Melani Kartikasari (Universitas Airlangga, 2015)
Introduction: Diabetes Mellitus (DM) is a chronic disease that requires individual ability of patients to adhere treatment of the disease recommended by doctors. Patient should be able to manage the diabetes to prevent complications by maximizing existing aspects within themselves to determine the best option available. The purpose the study was to analyze the effect of diabetes empowerment education to self empowerment and quality of life of patients with type 2 DM at the Puskesmas Bendo Kediri.Method: This study used quasy experiment design with non randomized control group pretest posttest design. Total sampel was 32 respondents divided into control group and experiment group, sample recruited by purposive sampling. Data were collected using questionnaire with DES (Diabetes Empowerment Scale) and DQoL (Diabetes Quality of Life). Data were then analyzed using Wilcoxon Sign rank test and Mann Whitney with level of significance of 0,05. Result: The results showed that there was a differences in self empowerment and quality of life of patients with type 2 DM after intervention. Mann Whitney analysis result`s showed that there are differences in self empowerment between control and experiment groups (p = 0,029) and there was a difference in the quality of life between control and experiment groups (p = 0,022). It can be referred from it that DEE influences self empowerment and quality of life of type 2 DM patients. Discussion: It can be concluded that diabetes empowerment education increasing selfempowerment and quality of life of patients with DM type 2. Further studies should using more objective parameters such as changes in blood sugar levels, hemoglobin A1C values to evaluate the effect of diabetes empowerment education on self-empowerment and quality of life of patients with DM.